Philippine Shari'a courts procedure - Arabani, Bensaudi I., Sr (Manila : Rex Book Store, 2000)
Includes the text of special rules of procedure in the Shari'a courts
Keywords: Court rules -- Philippines; Courts, Islamic -- Philippines -- Rules and practice